A STUDY ON THE EFFECT OF YOGA THERAPY ON LIVER FUNCTIONS - Sharma, K. Krishna; K, Udayakumara; Prasada H., Thirumaleshwara; Kumar K, Praveen (European Scientific Journal, ESJ, 2014)
The present study entitled” The effect of Yoga Therapy on Liver functions” is conducted in the Department, Mangalore University, Karnataka. Twenty employees were selected randomly for the present study and divided in to two groups. Viz, Experimental and Control, between the ages group of 20 and 50. Yogic practices were given only to the experimental group for a period of one and half months. In order to check the level of significance of mean, a student paired t- test was made use of. The study revealed that the globulin was reduced up to highly significant level and alkaline phosphate and weight was reduced significantly at the level of p – value 0.00087, 0.0364, 0.0424 respectively (at p – value 0.005). But there were no significant changes in the control group.